Pharmacognostical and phytochemical studies on Pothos scandens L. - Lalitharani,; V.R. Mohan,; A. Maruthupandian, (International Journal of Phytomedicine, 2010)
Pothos scandens L. known to the Kanikkars as ‘Paraioutan’ is an important medicinal plant. The Kanikkar tribe, inhabitants of Agasthiarmalai Biosphere Reserve, Western Ghats, Tamil Nadu, India. use leaf and stem of this plant to reduce body heat and also helps in conception. The present investigation deals with the pharmacognostic studies of the leaf and stem of the said plant. Pharmacognostic studies include microscopic, physicochemical constant (ash & extractive values), Fluorescence analysis and preliminary phytochemical evaluations.